Abnormal outer and inner retina in a mouse model of Huntington’s disease with age - Yang, Dashuang; Huang, Chunhui; Guo, Xuemeng; Li, Yintian; Wu, Jiaxi; Zhang, Zaijun; Yan, Sen; Xu, Ying (Frontiers in Aging Neuroscience, 2024)
Huntington’s disease (HD) is a progressive neurodegenerative disorder characterized by motor dysfunction and cognitive decline. While retinal abnormalities have been documented in some HD patients and animal models, the nature of these abnormalities—specifically whether they originate in the inner or outer retina—remains unclear, particularly regarding their progression with age. This study investigates the retinal structure and function in HD transgenic mice (R6/1) compared to C57BL/6 J control mice at 2, 4, and 6 months of age, encompassing both pre-symptomatic and symptomatic stages of HD. Pathological assessments of the striatum and evaluations of motor function confirmed significant HD-related alterations in R6/1 mice at 6 months. Visual function was subsequently analyzed, accompanied by immunofluorescent staining of retinal and optic nerve tissues over time. Our findings revealed that R6/1 mice exhibited pronounced HD symptoms at 6 months, characterized by neuronal loss in the striatum and impaired locomotor abilities. Functionally, visual acuity declined at 6 months, while retinal light responses began to deteriorate by 4 months. Structurally, R6/1 mice demonstrated a global reduction in cone opsin expression as early as 2 months, with a decrease in rhodopsin levels at 4 months, alongside a thinner retinal structure compared to controls. Notably, rod bipolar cell populations were decreased at 6 months, exhibiting shorter dendritic branches and reduced synaptic connections with photoreceptors in the outer retina. Additionally, ganglion cell numbers in the inner retina decreased at 6 months, accompanied by aberrant neural fibers in the optic nerve. Microglial activation was evident at 4 months, while astrocytic activation was observed at 6 months. Aggregates of mutant huntingtin (mHTT) were first detected in the ganglion cell layer and optic nerve at 2 months, subsequently disseminating throughout all retinal layers with advancing age. These results indicate that retinal pathology in R6/1 mice manifests earlier in the outer retina than in the inner retina, which does not align with the progression of mHTT aggregation. Consequently, the R6/1 mouse retina may serve as a more effective model for elucidating the mechanisms underlying HD and evaluating potential therapeutic strategies, rather than functioning as an early diagnostic tool for the disease.